FACTORS EVALUATION AFFECTING SUNFLOWER OIL PRICES IN UKRAINE - Oksana MAKARCHUK; Tetyana KUTS (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In the article were evaluated factors that influence on Ukrainian sunflower oil prices. There was made price analysis, where domestic sunflower seed prices and European sunflower oil prices were taken into account. The research results showed that nowadays the sunflower oil production increased twofold compare to 2010. It could be explained by using modern processing technologies and growth demand for vegetable oils on the world market. Thus, it leads to increase Ukrainian export of sunflower oil more than twofold worldwide in 2021. Our research has shown Granger causality between the series of Ukrainian sunflower oil and European sunflower oil using VAR modeling. Indeed, European sunflower oil prices Granger-causes Ukrainian sunflower oil price at 0.01 significance level. In turn, it means that the past changes in European sunflower oil prices make it possible to forecast current changes of Ukrainian sunflower oil prices. Opposite interactions are also significant. However, there was not confirmed causality between the series of Ukrainian sunflower oil and Ukrainian sunflower seed. The absence of causality between Ukrainian sunflower oil and Ukrainian sunflower seeds could be explained due to the fact that sunflower seed prices domestically more influenced by the conjucture formed at vegetable oil market and not vice versa.